A mortar anchor mesh sprayed concrete support process

By using the connecting components of composite modified fibers and reinforced powder in spray concrete, combined with curing agents and accelerators, the problem of cracking of spray concrete during hydration and exothermic process is solved, and the goal of reducing cement usage and improving support effect is achieved.

CN115163124BActive Publication Date: 2025-04-29SHANDONG WATER GENERAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210847334.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-19
Publication Date
2025-04-29
Estimated Expiration
2042-07-19

AI Technical Summary

Technical Problem

Existing sprayed concrete is prone to cracking during hydration and heat release, resulting in poor support effect and the amount of cement needs to be increased to reduce the rebound, but this increases the problem of hydration and heat release.

Method used

The connecting components composed of composite modified fibers, reinforced powders and adhesives are used to increase the connection strength of sprayed concrete, reduce the rebound amount, and promote the curing of epoxy resin through curing agents and accelerators to further improve the connection strength.

Benefits of technology

It effectively reduces cracking caused by hydration and heat exotherm of the sprayed concrete layer, reduces the amount of cement used, and improves the connection strength and support effect of the sprayed concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003753380720000071
    Figure BDA0003753380720000071
  • Figure BDA0003753380720000081
    Figure BDA0003753380720000081
  • Figure BDA0003753380720000082
    Figure BDA0003753380720000082
Patent Text Reader

Abstract

The present application relates to the field of tunnel initial support technology, and specifically discloses a mortar anchor rod mesh sprayed concrete support technology, which includes the following steps: S1, after tunnel excavation, use sprayed concrete to spray the rock surface for the first time; S2, install multiple anchor rods at intervals along the circumference of the rock surface; S3, hang a steel mesh on the initial sprayed concrete layer and support the arch frame, and then use sprayed concrete for re-spraying; S4, spray curing is carried out 2 hours after the re-spraying is completed; the sprayed concrete is composed of the following raw materials in parts by weight: 700-800 parts of crushed stone, 800-1000 parts of sand, 180-220 parts of cement, 12-18 parts of accelerator, 160-180 parts of water, and 70-90 parts of connecting components, and the connecting components include composite modified fibers, reinforcing powders and adhesives. The support technology of the present application has the advantage of reducing cracking of the sprayed concrete layer caused by hydration heat release.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of tunnel initial support technology, and more specifically, it relates to a mortar anchor mesh sprayed concrete support technology. Background Art

[0002] After tunnel excavation, in order to control the release and deformation of surrounding rock stress and increase structural safety, and to facilitate construction, it is necessary to construct a structural layer as part of the permanent bearing structure, which is called primary support.

[0003] The initial support in tunnel engineering generally adopts the anchor-sprayed mesh structure. It is necessary to first spray the rock surface with shotcrete, then construct anchor rods and steel mesh, and finally spray again to the designed thickness.

[0004] At present, shotcrete is mainly prepared by adding accelerators to ordinary concrete. In order to reduce the rebound of shotcrete, the amount of cement will be increased, which will increase the hydration heat of the concrete, making the shotcrete layer prone to cracking, and thus resulting in poor support effect. Summary of the invention

[0005] In order to reduce the amount of cement used, reduce cracking of the shotcrete layer due to hydration heat release, and reduce the impact on the support effect, the present application provides a mortar anchor mesh shotcrete support process.

[0006] The present application provides a mortar anchor mesh shotcrete support process, which adopts the following technical solution:

[0007] A mortar anchor mesh shotcrete support process comprises the following steps:

[0008] S1. After tunnel excavation, use shotcrete to spray the rock surface initially;

[0009] S2, install multiple anchor rods at intervals along the circumference of the rock surface;

[0010] S3, hang steel mesh on the initial shotcrete layer and support the arch frame, and then use shotcrete for re-spraying;

[0011] S4. Spray curing is carried out 2 hours after the re-spraying is completed;

[0012] The shotcrete is composed of the following raw materials in parts by weight: 700-800 parts of crushed stone, 800-1000 parts of sand, 180-220 parts of cement, 12-18 parts of accelerator, 160-180 parts of water, and 70-90 parts of connecting components, wherein the connecting components include composite modified fiber, reinforcing powder and adhesive, and the weight ratio of the composite modified fiber, reinforcing powder and adhesive is (10-12):(2-4):4.

[0013] By adopting the above technical scheme, since the connection components are composed of composite modified fibers, reinforcing powders and adhesives, the connection strength during the spraying process of shotcrete is effectively improved, the rebound of shotcrete is effectively reduced, and the amount of cement used is reduced, and the cracking of the shotcrete layer caused by hydration heat is reduced, which effectively reduces the adverse effects of cracking on the support effect.

[0014] Preferably, the composite modified fiber is obtained by composite modification of wool fiber and coconut shell fiber.

[0015] By adopting the above technical scheme, wool fiber and coconut shell fiber are composite-modified, thereby effectively improving the tensile strength of wool fiber. When shotcrete is constructed, the composite modified fiber plays a mounting role, thereby effectively reducing the rebound of shotcrete.

[0016] Preferably, the preparation method of the composite modified fiber includes the following steps: S1, pretreating wool fiber and coconut shell fiber respectively; S2, subjecting the pretreated wool fiber to titanium dioxide loading modification; S3, subjecting the titanium dioxide loaded modified wool fiber and the pretreated coconut shell fiber to titanium dioxide loading modification to obtain the composite modified fiber.

[0017] By adopting the above technical scheme, wool fiber and coconut shell fiber are connected by using titanium dioxide as an intermediate connecting material, so that the wool fiber and coconut shell fiber can be combined, the tensile strength of the composite modified fiber is effectively enhanced, thereby effectively reducing the rebound amount of shotcrete, making the shotcrete less likely to rebound and fall.

[0018] Preferably, the reinforcing powder is nano titanium diboride powder with a particle size D 90 =100nm.

[0019] By adopting the above technical solution, nano titanium diboride is used as a filler between wool fiber and coconut shell fiber, so that the strength of the composite modified fiber is enhanced, so that the composite modified fiber plays a better connecting role in shotcrete.

[0020] Preferably, the method for preparing the connecting component comprises the following steps: mixing the composite modified fiber, the reinforcing powder and the adhesive uniformly to obtain the connecting component.

[0021] By adopting the above technical scheme, the connecting components can be prepared only by simple mixing, and the adhesive will strengthen the connection of the powder to the gaps and surfaces of the wool fibers and coconut shell fibers, thereby improving the performance of the composite modified fibers and further enhancing the connection strength of the composite modified fibers in shotcrete.

[0022] Preferably, the adhesive is epoxy resin.

[0023] By adopting the above technical solution, the epoxy resin not only serves as a bonding agent between the composite modified fiber and the reinforcing powder, but also improves the adhesion strength of the shotcrete, thereby further reducing the rebound amount of the shotcrete.

[0024] Preferably, the shotcrete further comprises 0.1 parts of a curing agent and 0.1 parts of an accelerator.

[0025] By adopting the above technical solution, the curing of epoxy resin is promoted by the curing agent and the accelerator, thereby further improving the bonding and curing effect of the epoxy resin on the composite modified fiber and the reinforcing powder, thereby improving the connection effect of the connecting components.

[0026] Preferably, the steel fiber has a diameter of 0.3 mm and a length of 20 mm.

[0027] By adopting the above technical scheme, the strength and impact resistance of shotcrete are improved by adding steel fibers, and at the same time, the composite modified fibers are partially adhered to the steel fibers. At this time, the steel fibers play a role in positioning and fixing the composite modified fibers, thereby enhancing the connection strength between the newly sprayed shotcrete and the already sprayed shotcrete.

[0028] In summary, this application has the following beneficial effects:

[0029] 1. Since the present application adopts connecting components to reinforce the shotcrete, the wool fiber and coconut shell fiber are composite-modified with titanium dioxide and then reinforced with titanium diboride powder and epoxy resin, thereby effectively increasing the connection strength between the sprayed shotcrete and reducing the rebound of the shotcrete. Then, while reducing the amount of cement used, the rebound of the shotcrete is kept within a suitable range, thereby effectively reducing the cracks in the shotcrete layer caused by the hydrothermal reaction and reducing the adverse effects on the support effect.

[0030] 2. In the present application, a curing agent and an accelerator are preferably used to promote the curing of the epoxy resin, so that the connection strength between the composite modified fiber and the titanium diboride powder can be improved, thereby further improving the strength of the composite modified fiber and reducing the rebound of the shotcrete.

[0031] 3. The steel fiber of the present application plays a role in positioning the composite modified fiber, and then the composite modified fiber is used as a bridge to enhance the connection strength between the sprayed concrete and the concrete to be sprayed, thereby reducing the rebound of the sprayed concrete;

[0032] 4. Coconut shell fiber is used as the main body, and wool fiber modified by titanium dioxide loading is connected to it. The scaly structure on the surface of the wool fiber itself and the loaded titanium dioxide increase the connection strength of the composite modified fiber to other raw materials, thereby reducing the rebound of the shotcrete. DETAILED DESCRIPTION

[0033] In the present application: the diameter of wool fiber is 30 μm and the length is 60 mm. The diameter of coconut shell fiber is 100 μm and the length is 100 mm. The particle size of titanium diboride powder is 150 nm. The particle size of crushed stone is 5-25 mm, and the weight ratio of 5-10 mm crushed stone: 10-25 mm crushed stone is 7:3. The particle size of sand is 0-5 mm, and the weight ratio of 0-0.075 mm sand: 0.075 mm sand is 1:4. The diameter of steel fiber is 0.3 mm and the length is 20 mm. The epoxy resin is E-44 epoxy resin, the curing agent is EP curing agent, and the accelerator is K54 epoxy accelerator, all of which are commercially available.

[0034] The present application is further described in detail below with reference to the embodiments.

[0035] Preparation Example

[0036] Preparation Example 1

[0037] The preparation method of the composite modified fiber comprises the following steps:

[0038] S1. Preprocessing:

[0039] The wool fiber was immersed in a 50°C, 0.5g / L Na2CO3 solution for 15 minutes, then washed with deionized water three times, and then immersed in 50°C anhydrous ethanol and acetone solution for 10 minutes each, and finally dried in a 50°C oven for later use. The coconut shell fiber was treated in the same steps;

[0040] S2. Titanium dioxide loading modification of wool fiber:

[0041] Tetrabutyl titanate was added dropwise to anhydrous ethanol and stirred, and then deionized water was added. The volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water was 1:20:120. The wool fiber pretreated in S1 was immersed for 10 minutes, and placed in a reactor together with the solution. After being heated at a constant temperature of 110°C for 2 hours, it was taken out and cooled to room temperature. The wool fiber modified by titanium dioxide loading was repeatedly washed with deionized water until the solution was clear, and then dried at 50°C.

[0042] S3. Preparation of composite modified fibers:

[0043] Tetrabutyl titanate is added dropwise into anhydrous ethanol and stirred, and then deionized water is added. The volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water is 1:20:120. The modified wool fiber in S2 and the pretreated coconut shell fiber in S1 are immersed for 10 minutes, placed in a reactor together with the solution, heated at a constant temperature of 110°C for 2 hours, taken out and cooled to room temperature, the composite modified fiber is repeatedly washed with deionized water until the solution is clear, and dried at 50°C to obtain a composite modified fiber.

[0044] Preparation Example 2

[0045] The preparation method of the composite modified fiber comprises the following steps:

[0046] S1. Preprocessing:

[0047] The wool fiber was immersed in a 50°C, 0.5g / L Na2CO3 solution for 15 minutes, then washed with deionized water three times, and then immersed in 50°C anhydrous ethanol and acetone solution for 10 minutes each, and finally dried in a 50°C oven for later use. The coconut shell fiber was treated in the same steps;

[0048] S2. Titanium dioxide loading modification of wool fiber:

[0049] Tetrabutyl titanate was added dropwise into anhydrous ethanol and stirred, and then deionized water was added. The volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water was 1:20:120. The wool fiber pretreated in S1 was immersed for 10 minutes and placed in a reactor together with the solution. After being heated at a constant temperature of 110°C for 2 hours, it was taken out and cooled to room temperature. The wool fiber modified by titanium dioxide loading was repeatedly washed with deionized water until the solution was clear and dried at 50°C to obtain a composite modified fiber.

[0050] Preparation Example 3

[0051] The preparation method of the composite modified fiber comprises the following steps:

[0052] S1. Preprocessing:

[0053] The coconut shell fiber was immersed in a 50°C, 0.5g / L Na2CO3 solution for 15 minutes, then washed with deionized water three times, immersed in 50°C anhydrous ethanol and acetone solution for 10 minutes each, and finally dried in a 50°C oven for use. The coconut shell fiber was treated in the same steps;

[0054] S2, Titanium dioxide loading modification of coconut shell fiber:

[0055] Tetrabutyl titanate was added dropwise into anhydrous ethanol and stirred, and then deionized water was added. The volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water was 1:20:120. The coconut shell fiber pretreated in S1 was immersed in it for 10 minutes, and placed in a reactor together with the solution. After being heated at a constant temperature of 110°C for 2 hours, it was taken out and cooled to room temperature. The composite modified fiber was repeatedly washed with deionized water until the solution was clear, and dried at 50°C to obtain a composite modified fiber.

[0056] Example

[0057] Example 1

[0058] A mortar anchor mesh shotcrete support process comprises the following steps:

[0059] S1. After tunnel excavation, use shotcrete to spray the rock surface initially;

[0060] S2, install multiple anchor rods at intervals along the circumference of the rock surface;

[0061] S3, hang steel mesh on the initial shotcrete layer and support the arch frame, and then use shotcrete for re-spraying;

[0062] S4. Carry out spray maintenance 2 hours after the re-spraying is completed.

[0063] Example 2

[0064] This embodiment discloses a method for preparing shotcrete, which comprises the following steps:

[0065] S1, taking 40 kg of the composite modified fiber prepared in Preparation Example 1, 10 kg of titanium diboride powder and 20 kg of epoxy resin, stirring and mixing to prepare a connecting component;

[0066] S2. The connecting components prepared in S1, 700 kg of crushed stone, 800 kg of sand, 280 kg of cement, 12 kg of accelerating setting agent and 140 kg of water were stirred and mixed to obtain shotcrete.

[0067] Example 3

[0068] The difference from Example 2 is that the amount of composite modified fiber added in S1 is 45 kg.

[0069] Example 4

[0070] The difference from Example 2 is that the amount of composite modified fiber added in S1 is 50 kg.

[0071] Example 5

[0072] S1, taking 40 kg of the composite modified fiber prepared in Preparation Example 1, 10 kg of titanium diboride powder and 20 kg of epoxy resin, stirring and mixing to prepare a connecting component;

[0073] S2. The connecting components prepared in S1, 750 kg of crushed stone, 900 kg of sand, 300 kg of cement, 15 kg of accelerating setting agent and 150 kg of water are stirred and mixed to obtain shotcrete.

[0074] Example 6

[0075] The difference from Example 5 is that the amount of composite modified fiber added in S1 is 45 kg.

[0076] Example 7

[0077] The difference from Example 5 is that the amount of composite modified fiber added in S1 is 50 kg.

[0078] Example 8

[0079] The difference from Example 5 is that the amount of titanium diboride powder added in S1 is 15 kg.

[0080] Example 9

[0081] The difference from Example 8 is that the amount of composite modified fiber added in S1 is 45 kg.

[0082] Example 10

[0083] The difference from Example 8 is that the amount of composite modified fiber added in S1 is 50 kg.

[0084] Embodiment 11

[0085] The difference from Example 5 is that the amount of titanium diboride powder added in S1 is 20 kg.

[0086] Example 12

[0087] The difference from Example 11 is that the amount of composite modified fiber added in S1 is 45 kg.

[0088] Embodiment 13

[0089] The difference from Example 11 is that the amount of composite modified fiber added in S1 is 50 kg.

[0090] Embodiment 14

[0091] The difference from Example 9 is that 30 kg of steel fiber is also added to S2.

[0092] Embodiment 15

[0093] The difference from Example 14 is that the amount of steel fiber added in S2 is 45 kg.

[0094] Example 16

[0095] The difference from Example 14 is that the amount of steel fiber added in S2 is 60 kg.

[0096] Embodiment 17

[0097] The difference from Example 9 is that 0.1 kg of curing agent and 0.1 kg of accelerator are also added to S2.

[0098] Embodiment 18

[0099] The difference from Example 15 is that 0.1 kg of curing agent and 0.1 kg of accelerator are also added to S2.

[0100] Embodiment 19

[0101] The difference from Example 9 is that the composite modified fiber in S1 is prepared in Preparation Example 2.

[0102] Embodiment 20

[0103] The difference from Example 9 is that the composite modified fiber in S1 is prepared in Preparation Example 3.

[0104] Embodiment 21

[0105] S1, taking 40 kg of the composite modified fiber prepared in Preparation Example 1, 10 kg of titanium diboride powder and 20 kg of epoxy resin, stirring and mixing to prepare a connecting component;

[0106] S2. The connecting components prepared in S1, 800 kg of crushed stone, 1000 kg of sand, 320 kg of cement, 18 kg of accelerator and 160 kg of water were stirred and mixed to obtain sprayed concrete.

[0107] Embodiment 22

[0108] The difference from Example 21 is that the amount of composite modified fiber added in S1 is 45 kg.

[0109] Embodiment 23

[0110] The difference from Example 21 is that the amount of composite modified fiber added in S1 is 50 kg.

[0111] Comparative Example

[0112] Comparative Example 1

[0113] The difference from Example 9 is that no epoxy resin is added to S1.

[0114] Comparative Example 2

[0115] The difference from Example 9 is that no titanium diboride powder is added to S1.

[0116] Comparative Example 3

[0117] The difference from Example 9 is that no composite modified fiber is added to S1.

[0118] Comparative Example 4

[0119] The difference from Example 9 is that titanium diboride powder and epoxy resin are not added to S1.

[0120] Comparative Example 5

[0121] The difference from Example 9 is that: no composite modified fiber and epoxy resin are added to S1.

[0122] Comparative Example 6

[0123] The difference from Example 9 is that: no composite modified fiber and titanium diboride powder are added to S1.

[0124] Comparative Example 7

[0125] The difference from Example 9 is that no connecting component is added.

[0126] Table 1 Examples and Comparative Examples Raw Materials (kg)

[0127]

[0128]

[0129] Performance testing

[0130] The 28d compressive strength of concrete was tested according to GB / T50081-2002 6 compressive strength test.

[0131] Find a side wall, lay canvas on the ground, then spray concrete, collect and weigh the concrete that falls to the ground, and measure the rebound rate of the sprayed concrete by calculating the ratio of the weight of the concrete that falls to the ground to the total weight of the sprayed concrete.

[0132] Table 2 Performance test table of embodiments and comparative examples

[0133]

[0134]

[0135] It can be seen from Example 9 and Comparative Examples 1-7 and Table 2 that the shotcrete is reinforced by using a connecting component, and the wool fiber and the coconut shell fiber are composite-modified with titanium dioxide and then reinforced with titanium diboride powder and epoxy resin, thereby effectively increasing the connection strength between the sprayed shotcrete and reducing the rebound of the shotcrete. Furthermore, while reducing the amount of cement used, the rebound of the shotcrete is maintained within a suitable range, thereby effectively reducing the cracks in the shotcrete layer caused by the hydrothermal reaction, thereby reducing the impact on the strength of the concrete.

[0136] It can be seen from Example 9 and Example 17 and Table 2 that it is preferred to use a curing agent and an accelerator to promote the curing of the epoxy resin, so that the connection strength between the composite modified fiber and the titanium diboride powder can be improved, thereby further improving the strength of the composite modified fiber and reducing the rebound of the shotcrete.

[0137] It can be seen from Example 9, Example 15 and Example 18 and Table 2 that the steel fiber plays a positioning role for the composite modified fiber, and then the composite modified fiber is used as a bridge to enhance the connection strength between the shotcrete and the to-be-shot concrete, thereby reducing the rebound of the shotcrete.

[0138] It can be seen from Example 9, Example 19 and Example 20 and Table 2 that the wool fiber modified by titanium dioxide loading is connected thereto, and the scaly structure on the surface of the wool fiber itself and the loaded titanium dioxide both increase the connection strength of the composite modified fiber to other raw materials, thereby reducing the rebound of the shotcrete.

[0139] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A mortar anchor mesh shotcrete support process, characterized in that: The following steps are involved: S1. After tunnel excavation, use shotcrete to spray the rock surface for the first time; S2, install multiple anchor rods at intervals along the circumference of the rock surface; S3, hang steel mesh on the initial shotcrete layer and support the arch frame, and then use shotcrete for re-spraying; S4. Spray curing is carried out 2 hours after the re-spraying is completed; The shotcrete is composed of the following raw materials in parts by weight: 700-800 parts of crushed stone, 800-1000 parts of sand, 180-220 parts of cement, 12-18 parts of accelerator, 160-180 parts of water, and 70-90 parts of connecting components, wherein the connecting components include composite modified fiber, reinforcing powder and adhesive, and the weight ratio of the composite modified fiber, reinforcing powder and adhesive is (10-12): (2-4): 4; The composite modified fiber is obtained by composite modification of wool fiber and coconut shell fiber; The preparation method of the composite modified fiber comprises the following steps: S1, pre-treating wool fiber and coconut shell fiber respectively; S2, performing titanium dioxide loading modification on the pre-treated wool fiber; S3, performing titanium dioxide loading modification treatment on the titanium dioxide loaded modified wool fiber and the pre-treated coconut shell fiber to obtain the composite modified fiber; The reinforcing powder is nano titanium diboride powder with a particle size of D 90 =100nm; The preparation method of the connecting component comprises the following steps: mixing the composite modified fiber, the reinforcing powder and the adhesive uniformly to obtain the connecting component.

2. The mortar anchor mesh shotcrete support process according to claim 1 is characterized in that: The adhesive is epoxy resin.

3. The mortar anchor mesh shotcrete support process according to claim 2 is characterized in that: The shotcrete also includes 0.1 parts of a curing agent and 0.1 parts of an accelerator.

Citation Information

Patent Citations

  • Polypropylene fiber sprayed concrete

    CN104446260A

  • Concrete

    CN107352924A

  • Tunnel open cutting construction process

    CN110424460A